2017
DOI: 10.1080/00223980.2017.1372351
|View full text |Cite
|
Sign up to set email alerts
|

Pre-entry Characteristics, Perceived Social Support, Adjustment and Academic Achievement in First-Year Spanish University Students: A Path Model

Abstract: Transition to university is a multifactorial process to which scarce consideration has been given in Spain, despite this being one of the countries with the highest rates of academic failure and attrition within the European Union. The present study proposes an empirical model for predicting Spanish students' academic achievement at university by considering pre-entry characteristics, perceived social support and adaptation to university, in a sample of 300 traditional first-year university students. The findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 40 publications
5
56
0
4
Order By: Relevance
“…In other words, alcohol and cannabis co-consumers perceived feelings of dissatisfaction and disengagement from university life, such as a lower motivation to complete academic requirements and lower academic effort, leading to academic failure. Despite the difficulties in explaining academic achievement in co-consumers on the basis of academic adjustment, many previous studies include academic adjustment as a powerful predictor of university outcomes [39,42,46,51,84], or as a mediator of the relationship between drinking motives and alcohol consequences [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, alcohol and cannabis co-consumers perceived feelings of dissatisfaction and disengagement from university life, such as a lower motivation to complete academic requirements and lower academic effort, leading to academic failure. Despite the difficulties in explaining academic achievement in co-consumers on the basis of academic adjustment, many previous studies include academic adjustment as a powerful predictor of university outcomes [39,42,46,51,84], or as a mediator of the relationship between drinking motives and alcohol consequences [66].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the weight of variables such as pre-university achievement [51,97], background variables [30], social support [98] and health problems [72] should also be tested in a more complete version of the model.…”
Section: Discussionmentioning
confidence: 99%
“…identified high school grade point average as a significant predictor of institutional attachment, as a significant predictor of institutional, academic and social adjustment to university, after controlling for the effects of gender and family background; see also Rodríguez et al . .…”
Section: Discussionmentioning
confidence: 99%
“…Social and demographic factors affect the academic success subsequent to primary education, and so they are indirectly being taken into account in the measurements of the previous achievements considered. In a recent investigation of predictors of university adjustment in Spanish students, P aramo et al [31] identified high school grade point average as a significant predictor of institutional attachment, as a significant predictor of institutional, academic and social adjustment to university, after controlling for the effects of gender and family background; see also Rodr ıguez et al [32].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies across the world in the last decades have identified perceived social support as a protective, empowering factor that is key to enabling emerging adults to fulfil the challenges involved in university life (Abdullah, Kong, & Talib, 2014;Katz & Somers, 2017;Lidy & Kahn, 2006;Rodriguez, Tinajero, & Paramo, 2017;Tao et al, 2000). However, little is known about how different dimensions of support might influence the diverse areas of adaptation to university in emerging adulthood.…”
Section: Introductionmentioning
confidence: 99%